Winter common wheat productivity depending on the seeding rate and the fractional composition of seeds - Yu. G. Skvortsova; N. V. Kalinina; G. A. Filenko (Зерновое хозяйство России, 2025)
The effect of seed quality on winter common wheat productivity is well known. The current paper has presented the results of a field trial to study the effect of seeding rates and the fractional composition of seeds on the productivity of the winter common wheat variety ‘Shef’, which was carried out in the south of the Rostov region on ordinary blackearth in the FSBSI “ARC “Donskoy” (2021-2024). The purpose of the current work was to estimate the effect of seeding rates and seed fractions on winter common wheat productivity in the primary links of seed production. It was found that with the optimal seed fraction of 2.4×20 mm and the maximum seeding rate of 5.0 million germ. seeds, there was obtained the largest productivity (9.8 t/ha). It was found that with the seeding rate of 3.0 million germ. seeds and the fractional composition of 2.4×20 mm, there was formed the largest 1000-seed weight (47.5 g), and the smallest one (42.7) was formed with the seeding rate of 5.0 million germ. seeds and the fraction of 2.6×20 mm. It was found that with the fraction of 2.4 × 20 mm and the mean seeding rate (3.0 million germ. seeds), there was obtained the maximum yield of quality seeds. Thus, to obtain higher-quality seed material for winter common wheat in primary seed production, it is necessary to use optimal seeding rates and seed fractions. The experimental data allow recommending seeds for sowing with the fractional composition of 2.4×20 mm and the seeding rate of 2.5 to 3.5 million germ. seeds.